Développement de la conceptualisation dans l’activité de conception d’étudiants-stagiaires en EPS durant l’année de formation en alternance - Elisabeth Magendie (Recherches en Éducation)
This research in the field of professional didactics was untaken within the theoretical framework of conceptualisation in action. It aims to give an account of the development of the process of conceptualisation for sports science student-teachers engaged in conceptualising during their teacher training. The research aims to identify modifications in the intersubjective and operational principles which student-teachers use when planning learning situations. Two student-teachers in the second year of their master’s degree in teaching and learning took part in the study. They were filmed in class at the beginning and the end of the year and each class was followed by an interview. The corpus was analysed in order to identify the organizing principles which the student-teachers used to orient and guide their actions. The results show differentiated evolution during the year. At the beginning of the year, both student-teachers’ based their planning of learning situations on prescriptions taught in their training institution (a teacher, creator of tasks centred on academic learning). By the end of the year, one of the student-teachers had become more reliant on principles related to classroom management. However, for the other student-teacher the ideals of the training institution, although redefined, remained present. Following analysis of these two cases and taking into account the similar difficulties which each student-teacher faced, we suggest that these difficult moments can be viewed as points at which it is possible to identify the conditions which are likely to lead to the transformation of practice. As a consequence, we suggest a number of ways in which student-teachers in training can be helped in their evolution of conceptualisation processes.